THE ROLE OF HUMAN RESOURCE MANAGEMENT (HRIS) IN EFFICIENCY AND EFFECTIVENESS TOWARDS GREEN BUSINESS - Ali Imron; Rivaldi Arif; Dikri Gifari; Dickson P. Aritonang; Asro Bin Harun (EKUITAS (Jurnal Ekonomi dan Keuangan), 2024)
Traditional human resource management (HRM) has been considered a failure in developing the human resource information system (HRIS) to change the paradigm of green business. Thus, this study aims to explain the changes, roles, and challenges of HRIS in the effectiveness and efficiency of the currently developing Green Business. It is qualitative research with the support of national or international journals, accredited and reputable proceedings, reference books, and reference journal mapping through https://researchrabbitapp.com. As a result, HRIS can overcome traditional HRM problems because it is conducted digitally and easily. The application of Green Human Resource Management (GHRM) can significantly increase competitiveness, improve the quality and productivity of the workforce, and maintain environmental integrity. Supporting the development of Green Businesses or businesses that focus on environmental sustainability. In conclusion, the transformation of HRM in utilizing HRIS is inevitable so that it can play an effective and efficient role. The utilization of HRIS can develop and be sustainable through innovation and information systems technology development towards green business and suggestions for HRIS development. Furthermore, it should be followed and carried out with sustainability along with developments of green business in line with Industrial Revolution 6.0.